2017
DOI: 10.3906/elk-1507-232
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for digital image watermarking to predict optimal blocks using artificial neural networks

Abstract: Abstract:In this paper, we propose a novel nonblind digital image watermarking based on discrete wavelet transform and singular value decomposition. This robust scheme takes advantage of artificial neural networks for selecting suitable image blocks in which the watermark signal can be embedded. Local characteristics of the blocks such as luminance and texture sensitivity are the main criteria that the selections are based on. Generally, selection is based on a prediction of the results with the objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In order to demonstrate the advantages of the proposed algorithm, we compared it with related algorithms in Table 1. As can be seen from Table 1, except that the ability to resist noise attack is slightly lower than that in [14], the proposed algorithm has better robustness, specially in the resistance to rotation.…”
Section: Robustness Analysismentioning
confidence: 92%
“…In order to demonstrate the advantages of the proposed algorithm, we compared it with related algorithms in Table 1. As can be seen from Table 1, except that the ability to resist noise attack is slightly lower than that in [14], the proposed algorithm has better robustness, specially in the resistance to rotation.…”
Section: Robustness Analysismentioning
confidence: 92%
“…It can be observed that the best results correspond to BCH (15,7,2) and BCH (15,5,3) schemes yielding ρ = 1 for the compression and noise attacks and ρ values near 0.99 for the filter attacks. The BCH (15,7,2) has been selected due to its lower redundancy in comparison with BCH (15,5,3). Comparing Tables 3 and 4 in conjunction with Figure 4, it can be observed that the usage of BCH increases the quality of the recovered watermark when ∆ = 24 , which results in acceptable PSNR and SSIM values, achieving the balance between quality and robustness.…”
Section: Parameter Selectionmentioning
confidence: 99%
“…Consequently, the protection of copyright and content of multimedia files has become remarkably important. To solve this problem, there exist diverse techniques known as watermarking [4] that consists of embedding additional information of the owner in the digital content to be protected [5]. Each watermarking method should satisfy the following requirements:…”
Section: Introductionmentioning
confidence: 99%